Fluorescent D-amino-acids reveal bi-cellular cell wall modifications important for Bdellovibrio bacteriovorous predation - Kuru, Erkin; Lambert, Carey; Jonathon, Rittichier; Till, Rob; Ducret, Adrien; Derouaux, Adeline; Gray, Joe; Biboy, Jacob; Vollmer, Waldemar; VanNieuwenhze, Michael; Brun, Yves; Sockett, Liz (Nature Publishing Group, 2017)
Modification of essential bacterial peptidoglycan (PG) containing cell walls can lead to antibiotic resistance, for example β-lactam resistance by L,D-transpeptidase activities. Predatory Bdellovibrio bacteriovorus are naturally antibacterial and combat infections by traversing, modifying and finally destroying walls of Gram-negative prey bacteria, modifying their own PG as they grow inside prey. Historically, these multi-enzymatic processes on two similar PG walls have proved challenging to elucidate. Here, with a PG labelling approach utilizing timed pulses of multiple fluorescent D-amino acids (FDAAs), we illuminate dynamic changes that predator and prey walls go through during the different phases of bacteria:bacteria invasion. We show formation of a reinforced circular port-hole in the prey wall; L,D-transpeptidaseBd mediated D-amino acid modifications strengthening prey PG during Bdellovibrio invasion and a zonal mode of predator-elongation. This process is followed by unconventional, multi-point and synchronous septation of the intracellular Bdellovibrio, accommodating odd- and even-numbered progeny formation by non-binary division.